Profile of High School Students Problem Solving skills and the Implementation of PBL Model Assisted by Digital Books on Dynamic Fluid Material - Elvia Reza Lutfiani; Nofri Hidayatin; Nurul Muawiyan; Siska Agustin Sha Hareni (Journal of Innovative Technology and Sustainability Education, 2026)
Objective: This study aims to analyze the problem-solving skills profile of high school students on fluid dynamics material as a basis for developing and applying a digital book-assisted Problem-Based Learning (PBL) model. Method: This preliminary study used a qualitative descriptive approach and was conducted at SMAN 1 Driyorejo, involving 102 grade XII students in the 2025/2026 academic year. Data were collected through problem-solving skill essay tests, student response questionnaires, and teacher interviews. Results: The results showed that students' problem-solving skills were still in the low category, with 91 students in the low category, 11 students in the medium category, and no students in the high category. Analysis of the indicators showed that the Visualize the Problem aspect received the lowest score, while the Physics Description indicator had the highest average score. In addition, the results of the questionnaires and interviews showed that physics learning was still dominated by lecture methods and the use of conventional media. Novelty: This study provides an empirical basis for the development of innovative learning through the application of Android-based digital books integrated with the PBL model to improve students' problem-solving skills in fluid dynamics material.